P14 Phenotypic and functional profile of CD4posCD25high regulatory T cells in autoimmune hepatitis/systemic lupus erythematosus overlap syndrome. (6th September 2011) - Longhi, M S; Ma, Y; Samyn, M; Gordon, P; Mieli-Vergani, G; Vergani, D
Abstract : Introduction: Autoimmune hepatitis (AIH) is a severe inflammatory liver disorder characterised by hypergammaglobulinaemia, seropositivity for autoantibodies and interface hepatitis on histology. Though the mechanisms leading to immune-tolerance breakdown have not been fully elucidated, a numerical and functional defect of circulating CD4 pos CD25 high regulatory T-cells (T-regs) plays a key role in permitting effector lymphocytes to attack hepatocytes. We have identified a cohort of children with concomitant AIH and systemic lupus erythematosus (SLE), a multi-system autoimmune disease in the context of which most studies have reported numerical and functional T-reg impairment. Aim: To define the phenotypic and functional profile of T-regs in children with AIH and SLE (AIH/SLE). Method: 9 AIH/SLE patients (8 females; median age: 13.9 years), 16 AIH patients (13 females; median age: 13.3 years) and 9 healthy subjects (HS, 6 females; median age: 34 years) were studied. T-reg phenotype was determined by flow cytometry after cell incubation with anti-CD4, CD25 and CD127 monoclonal antibodies. Frequency of FOXP3 pos and IFNγ, IL-4, IL-17 and IL-9-producing cells was assessed by intracellular staining. T-reg suppressor function was evaluated as reduction of cell proliferation, measured by 3 H-thymidine uptake, in co-culture experiments where CD4 pos CD25 high CD127 neg T-regs were added to CD25 neg target cells. Results: The number of T-regs in AIH/SLE patients (7.06±1.1) tended to be higher than in AIH (4.88±1.1; p=0.1) and was similar to HS (7.03±0.6). While the proportion of FOXP3 pos cells within T-regs did not differ, that of CD4 pos CD25 high CD127 pos cells was higher in AIH/SLE (2.4±0.99) than in AIH (0.46±0.2; p=0.019) and HS (0.63±0.3; p=0.05). The frequency of IFNγ-producing cells within T-regs was higher in AIH/SLE (6.75±1.7) than in AIH (4.8±1.9; p=0.019) and HS (3.5±0.82; p=0.05); conversely that of IL-4-producing cells within T-regs was lower in AIH/SLE (0±0) than in AIH (0.86±0.3; p=0.02) and HS (0.9±0.47; p=0.06). The frequency of IL-17 and IL-9-producing cells was negligible and did not differ among the groups. Addition of CD127 neg T-regs, while decreasing CD25 neg cell proliferation by 31.6% in HS (p=0.08) and by 12.3% (p=0.056) in AIH, did not affect the proliferation of CD25 neg cells isolated from AIH/SLE patients. Conclusion: Compared to AIH and HS, T-regs from AIH/SLE patients are more activated, are skewed towards a Th1 cytokine profile and are functionally defective. These data suggest that more severe alteration of T-reg phenotype and function may predispose to multiple autoimmune manifestations.